2011
DOI: 10.1021/la200377b
|View full text |Cite|
|
Sign up to set email alerts
|

Spatially Selective Photochemical Reduction of Silver on Nanoembossed Ferroelectric PZT Nanowires

Abstract: It is well known that photochemical reaction in an aqueous solution can be chosen by selectively patterning the domain structures of ferroelectrics. In this work, we investigate the photochemically induced deposition of Ag particles on ferroelectric lead zirconate titanate [Pb(Zr(x),Ti(1 - x))O(3)] nanowires fabricated by nanoembossing technology. The photochemical reduction of Ag particles is found to occur preferentially along the embossed nanowires. By imaging domain configurations of the embossed films usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…15,[19][20][21][22][23][24][25] Studies have shown that metallic nanoparticle deposition from an aqueous solution onto þZ surfaces of LiNbO 3 domain patterns can be achieved. [23][24][25] The nanopatterned features created using Ag nanoparticles possessed a uniform distribution with a size variation between 2 and 10 nm in both diameter and height. 24 Photochemical reduction on LiNbO 3 has been shown under certain conditions to result in nanopatterns which form along domain walls, 17 which have further been shown to be conducting.…”
mentioning
confidence: 99%
“…15,[19][20][21][22][23][24][25] Studies have shown that metallic nanoparticle deposition from an aqueous solution onto þZ surfaces of LiNbO 3 domain patterns can be achieved. [23][24][25] The nanopatterned features created using Ag nanoparticles possessed a uniform distribution with a size variation between 2 and 10 nm in both diameter and height. 24 Photochemical reduction on LiNbO 3 has been shown under certain conditions to result in nanopatterns which form along domain walls, 17 which have further been shown to be conducting.…”
mentioning
confidence: 99%
“…In comparison, our experimental conditions contained very high concentration of proteins and the sticky fibrinogen leads to a rapid formation of a proteinaceous overlayer that was found to be independent of the polarization. While the adsorption of molecules on polarized surfaces seems to be quite complex, the general notion that molecular interaction with the surfaces might depend on the fields present is supported by the observation that in the region of the ferroelectric domain boundaries the photo-reduction rate of AgNO 3 , HAuCl 4 , Pt (NO 3 ) 2 and other compunds is increased [23,[36][37][38][39]. In addition it was found that nanowires of pure Ag, Au and Pt were grown along the predefined 180 0 ferroelectric domain walls on c-cut congruent LiNbO 3 Less was so far known on interaction of cells with patterned, polarized substrates.…”
Section: Christophis Et Al Biointerphases 2013 8:27mentioning
confidence: 99%
“…1 Silver nanoparticles have been applied in many fields including photonics, micro-electronics, photocatalysis, lithography, and surface-enhanced Raman spectroscopy. 2,3 Several types of chemical and physical technologies, such as chemical reduction, [4][5][6] electrochemical reduction, [7][8][9] photochemical reduction, [10][11][12] and heat evaporation 13,14 have been developed for the synthesis of silver nanoparticles. In recent years, bio-or green-synthesis of silver nanoparticles has become an emerging science.…”
Section: Introductionmentioning
confidence: 99%